Speaking across curriculum in the public university - Dulin, Alvin T. (Linguistics and Culture Review, 2021)
This paper presents the status of Language Across Curriculum (LAC) as an approach in developing the speaking skills of the students in a public university, particularly at Cagayan State University. It provides baseline data on how English teachers, content area teachers, administrators and the administrative personnel develop students’ speaking skills in school-based speaking transactions and learning experiences. The study utilizes the descriptive method of research employing survey and comparative techniques supplemented by Focus Group Discussion and actual voice recordings. Findings reveal that LAC is evidently adopted as an approach in developing the speaking skills of students; however, the efforts in carrying this out are not consistent due to lack of a policy requiring the use of English in school-based communications. Both students and teachers assess that students do not receive maximum development of their speaking skills due to limited exposure in the use of English. Trainings and orientation on the role of the school community members, most especially among content-area teachers and administrative personnel and more extensive use of English as a medium of communication in the school are highly encouraged.